1996
DOI: 10.1002/(sici)1096-9098(199602)61:2<106::aid-jso4>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Significance of proliferating cell nuclear antigen (PCNA) expression in gastric cancer in relation to lymph node metastasis

Abstract: Proliferating cell nuclear antigen (PCNA) in gastric cancer was evaluated in relation to lymph node metastasis. A total of 125 gastric cancer patients who underwent gastrectomy were studied immunohistochemically. The PCNA‐positive rate of the primary lesion with lymph node metastasis (47.6%) was significantly higher than that in those without metastasis (24.3%, P < 0.0001). The PCNA‐positive rate of early gastric cancer was significantly higher in lesions with lymph node metastasis (36.9%) than in lesions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…27,28 In the current study, we also found that patients with early-stage gastric carcinoma in the high labeling group had a significantly higher rate of lymph node metastasis compared with patients in the low labeling group. In the study by Isozaki et al, 29 the PCNA labeling index among 125 patients with gastric carcinoma was significantly higher in patients who had lymph node metastasis compared with patients who did not have lymph node metastasis. Thus, the PCNA labeling index was a more valuable predictor of lymph node metastasis in patients who had early-stage disease compared with patients who had advanced disease.…”
Section: Discussionmentioning
confidence: 90%
“…27,28 In the current study, we also found that patients with early-stage gastric carcinoma in the high labeling group had a significantly higher rate of lymph node metastasis compared with patients in the low labeling group. In the study by Isozaki et al, 29 the PCNA labeling index among 125 patients with gastric carcinoma was significantly higher in patients who had lymph node metastasis compared with patients who did not have lymph node metastasis. Thus, the PCNA labeling index was a more valuable predictor of lymph node metastasis in patients who had early-stage disease compared with patients who had advanced disease.…”
Section: Discussionmentioning
confidence: 90%
“…PCNA plays an important role in DNA replication, but is also associated with other functions such as chromatin remodeling, DNA repair, sister-chromatid cohesion and cell cycle control 54 , 55 . It has been shown taht PCNA was significantly related to lymph node metastasis in gastric cancer 56 . Interestingly, a preveoius study has shwon that PCNA as an oncogene can be involved in NSCLC progression through up-regulation of STAT3 57 .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the metabolism and DNA replication in tumor cells represent the proliferative activity. Thus, PCNA is frequently used as an indicator of proliferative activity of tumor cells (Isozaki et al, 1996;Niu et al, 2002). Ginsenoside Rg3 inhibits the PCNA expression that causes the reduced proliferative activity of lung cancer.…”
Section: Discussionmentioning
confidence: 99%